CONJUNCTION OF GRAMMATICAL COHESION IN SPEECH TEXT - Stivani Ismawira Sinambela; Nur Lela; Tengku Thyrhaya Zein (BAHAS, 2020)
AbstractCohesion of a discourse is divided into two aspects, namely grammatical cohesion and lexical cohesion. In this study what will be examined is grammatical cohesion, especially the conjunction of grammatical cohesion. This study aims to identify the forms of the conjunction of grammatical cohesion in the text of the speech of German Prime Minister Angela Merkel. This research is a qualitative research. The design in this study is content analysis with descriptive characteristics, namely the presentation of data based on the object of research. The results showed that the language elements in the form of words, phrases, clauses and sentences as part of the reference of two sentences in pairs to find out the cohesive relationship was evenly distributed. The percentage of the use of grammatical cohesion in the aspect of conjunction includes (1) additive conjunction (combined) is 153 findings or 45%; (2) causal conjunctions (cause) is 89 findings or 26%; (3) adversative conjunctions (contradictions) is 66 findings or 19%; (4) temporal conjunctions (time) is 35 findings or 10%. The data shows that additive conjunction is the most dominant type of conjunction used in Angela Merkel's text. Keywords: Grammatical Cohesion, Conjunction, Speech Text, Angela Merkel.